Resin composition for laser marking

By using potassium titanate, glass fiber and non-halogen flame retardant in the polyester resin composition, the poor laser printing effect and material toxicity of the thermoplastic resin are solved, and the resin composition with high mechanical characteristics and significant laser printing contrast is achieved, which is suitable for a variety of industrial components.

CN119731264APending Publication Date: 2025-03-28东洋纺艾睦希株式会社
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202380059994.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-09-29
Filing Date
2023-08-25
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient laser printing on thermoplastic resins, and there are problems of degradation of toxic components and mechanical characteristics in traditional laser marking materials.

Method used

By adding a specific amount of potassium titanate to the polyester resin composition, instead of titanium dioxide and reducing agent, combining glass fibers and a non-halogen flame retardant, a resin composition with high mechanical properties and significant laser printing contrast is formed.

Benefits of technology

It achieves a high contrast laser printing effect while maintaining high mechanical characteristics, and is suitable for electrical/electronic components, mechanical structural components and automotive components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005272323560000111
    Figure BDA0005272323560000111
Patent Text Reader

Abstract

Provided is a resin composition for laser marking, which has excellent laser marking properties on electrical or electronic components, mechanical structural components, automobile components, and the like, and which is capable of obtaining characters, symbols, and the like having a high strength and high rigidity at the same time. The resin composition for laser marking is characterized by containing 20-80% by mass of a polyester resin (A), 10-50% by mass of glass fibers (B), and 0.1-10% by mass of potassium titanate (C). The polyester resin (A) is preferably polybutylene terephthalate or polyethylene terephthalate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition for laser marking having excellent mechanical strength and laser marking properties. Background Art

[0002] Polyester resin is widely used as an engineering plastic for applications such as automobiles, electrical or electronic components, due to its excellent mechanical properties, electrical properties, other physical and chemical properties and good processability. In addition, identification marks of products are widely used in the industrial field. For example, it is used to attach the manufacturing date, expiration date, corporate logo, product serial number, model number, etc. to resin products. For these engravings, there are printing, hot stamping, other embossing methods or methods using additional labels, etc. In particular, in the case of resin products, when using a laser, it can be engraved without contact and very quickly and with high precision. Through this method, for example, graphics such as bar codes can be printed or even small characters can be attached to non-planar surfaces at high speed. In addition, through this method, there is no need to worry about peeling and disappearance like labels and printing. Therefore, in particular, in identification marks for thermoplastic resins, the requirements for suitable mechanical, thermal, electrical and chemical properties and laser engraving properties are gradually increasing.

[0003] It is generally known that thermoplastic resin products can absorb energy from irradiated laser light and convert the energy into heat, thereby inducing a color change reaction (ie, imprinting) of the material.

[0004] However, it has been difficult to actually mark most thermoplastic resins using lasers. For example, CO2 lasers that emit infrared light in the 10.6 μm region are very weak even at high power, so the marking is difficult to read. In addition, in the case of polyurethane elastomers and polyether-ester elastomers, although the marking is performed, there is almost no contrast with the surroundings, so readable marking is also not possible.

[0005] In order to perform laser marking on thermoplastic resins, the resin needs to absorb laser light. The laser absorption depends on the chemical structure of the resin composition and the wavelength of the laser used. When the inherent ability of the polymer constituting the thermoplastic resin is insufficient, additives such as laser absorbers are usually added to improve the absorption of laser light.

[0006] For example, Patent Document 1 proposes a polyamide resin composition for laser marking using a halogen-containing organic compound and an antimony compound. However, antimony compounds are toxic and suspected to be carcinogenic. Therefore, it is required that the composition does not contain antimony compounds.

[0007] On the other hand, a safe laser marking material containing no toxic antimony but mixed with titanium dioxide and a reducing agent is proposed in Patent Document 2. However, when the laser marking material of Patent Document 2 is actually mixed with a resin composition, the mechanical properties of the resin composition may be deteriorated. Prior art literature Patent Literature

[0008] Patent Document 1: Japanese Patent Application Publication No. 2007-98939 Patent Document 2: Japanese Patent Application Laid-Open No. 11-1065 Summary of the invention Problem that the invention aims to solve

[0009] In view of the above-mentioned current state of the prior art, the present invention aims to provide a resin composition for laser marking which has high strength, high rigidity and excellent laser marking properties for electric / electronic parts, mechanical structural parts, automobile parts, etc., and can produce letters or symbols with clear contrast. Technical means of solving problems

[0010] The inventors conducted in-depth research to achieve the above-mentioned purpose, and found that the reason why the mechanical properties of the resin composition mixed with the laser marking material of Patent Document 2 are poor is that the glass fiber usually added to the resin composition for reinforcement will be damaged by titanium dioxide, resulting in a decrease in mechanical properties such as bending strength. In addition, it is also found that in the use of electrical or electronic components, mechanical structural components, automotive components, etc., due to the requirement of high flame retardancy, there is a situation where a flame retardant is mixed with the resin composition, but in the flame retardant, especially when a non-halogen flame retardant is mixed, the mechanical properties are originally low compared to the system without a flame retardant, but the mechanical properties are further reduced by mixing the flame retardant. Then, the inventors found that as a laser marking material, by using a specific amount of potassium titanate instead of titanium dioxide and a reducing agent as in Patent Document 2, even when the polyester resin composition contains glass fiber and a non-halogen flame retardant, a laser marking resin composition with a laser engraving property with a sharp contrast while maintaining high mechanical properties can be obtained, thereby completing the present invention.

[0011] That is, the present invention has the following configurations [1] to [4]. [1] A resin composition for laser marking, characterized in that it contains 20 to 80% by mass of a polyester resin (A), 10 to 50% by mass of a glass fiber (B), and 0.1 to 10% by mass of potassium titanate (C). [2] The laser marking resin composition according to [1], wherein the potassium titanate (C) is fibrous potassium titanate. [3] The laser marking resin composition according to [1] or [2], characterized in that the laser marking resin composition further contains 1 to 30% by mass of a non-halogen flame retardant (D), and the flexural strength of the laser marking resin composition is greater than 165 MPa. [4] The laser marking resin composition according to [1] or [2], wherein the polyester resin (A) is polybutylene terephthalate or polyethylene terephthalate. Effects of the Invention According to the present invention, a laser marking resin composition having high strength, high rigidity and excellent laser marking properties can be provided. In addition, even if the resin composition of the present invention is mixed with a non-halogen flame retardant, the mechanical properties are less reduced. Furthermore, for the resin composition of the present invention, since a colorant such as carbon black is not necessary, a wide range of tones can be used. DETAILED DESCRIPTION

[0013] The laser marking resin composition of the present invention is characterized in that a specific amount of potassium titanate (C) is mixed as a laser marking material in a resin composition obtained by mixing a polyester resin (A) and a glass fiber (B) for reinforcement.

[0014] As the polyester resin (A), a polyester resin having a dicarboxylic acid component and a diol component as structural units is preferred. As the dicarboxylic acid component, an aromatic dicarboxylic acid is preferably used as the main component. Here, the main component means that it is usually 70 mol% or more, preferably 80 mol% or more, more preferably 90 mol% or more, and particularly preferably 95 mol% or more relative to all dicarboxylic acid units. In addition to the aromatic dicarboxylic acid, an aliphatic dicarboxylic acid can be used.

[0015] Examples of the aromatic dicarboxylic acid include terephthalic acid, isophthalic acid, phthalic acid, 2,6-naphthalene dicarboxylic acid, 1,3-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, 1,5-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, diphenyl-4,4′-dicarboxylic acid, 4,4′-diphenyl ether dicarboxylic acid, 1,2-bis(phenoxy)ethane-p,p′-dicarboxylic acid, and anthracene dicarboxylic acid. Among these, terephthalic acid, isophthalic acid, and 2,6-naphthalene dicarboxylic acid are preferred.

[0016] As aliphatic dicarboxylic acids, specifically, chain or alicyclic dicarboxylic acids having carbon atoms of 2 or more and 40 or less, such as oxalic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, dodecanedioic acid, dimer acid and cyclohexanedicarboxylic acid, can be mentioned. The above dicarboxylic acid components can be used alone or in combination of two or more. In addition to the dicarboxylic acid component and the diol component, a copolymerization hydroxycarboxylic acid component and a lactone component can also be used. As for the amount used, it is preferably 30 mol% or less, more preferably 20 mol% or less, and further preferably 10 mol% or less relative to the total monomer component.

[0017] Examples of the diol component include ethylene glycol, propylene glycol, 1,3-propylene glycol, 1,4-butylene glycol, 1,5-pentanediol, neopentyl glycol, 1,6-hexanediol, 3-methyl-1,5-pentanediol, 2-methyl-1,5-pentanediol, 2,2-diethyl-1,3-propylene glycol, 2-butyl-2-ethyl-1,3-propylene glycol, 1,9-nonanediol, 1,10-decanediol, 1,4-cyclohexanedimethanol, 1,3-cyclohexanedimethanol, and 1,2-cyclohexanedimethanol. Among these, ethylene glycol, 1,3-propylene glycol, and 1,4-butylene glycol are preferred.

[0018] Preferred polyester resins (A) include polybutylene terephthalate, polyethylene terephthalate, polytrimethylene terephthalate, polybutylene naphthalate, and polyethylene naphthalate. The polyester resin (A) preferably has an intrinsic viscosity (IV) of 0.36 to 1.60 dl / g, more preferably 0.52 to 1.25 dl / g, further preferably 0.58 to 1.12 dl / g, and particularly preferably 0.62 to 1.02 dl / g, when measured at 30°C using an Ubbelohde viscometer in a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4).

[0019] The content of the polyester resin (A) in 100% by mass of the resin composition is 20 to 80% by mass, preferably 25 to 75% by mass, more preferably 27 to 73% by mass, and further preferably 30 to 70% by mass.

[0020] As glass fiber (B), for example, there can be mentioned: filamentary fibers obtained by melt spinning of glass such as E glass (Electrical glass), C glass (Chemical glass), A glass (Alkali glass), S glass (High strength glass) and alkali-resistant glass. As glass fiber (B), a general product with an average fiber diameter of about 4 to 50 μm and a cut length of about 3 to 6 mm can be used. As the cross-sectional shape of glass fiber (B), glass fibers with circular cross-sections and non-circular cross-sections can be used. As glass fibers with non-circular cross-sections, fibers with a cross-section perpendicular to the length direction of the fiber length are also included, and the flatness is preferably 1.3 to 8. The flatness here refers to the ratio of the major diameter / minor diameter when a rectangle with the minimum area circumscribed on the cross-section perpendicular to the length direction of the glass fiber is assumed, with the long side of the rectangle as the major diameter and the length of the short side as the minor diameter. Regarding the thickness of the glass fiber, for example, a glass fiber having a minor diameter of about 1 to 20 μm and a major diameter of about 2 to 100 μm can be used. These glass fibers may be used alone or in combination of two or more.

[0021] The glass fiber (B) is preferably pre-treated with a coupling agent such as an organosilane compound, an organotitanium compound, an organoborane compound, and an epoxy compound. By mixing the resin composition with the glass fiber treated with the coupling agent, an excellent molded product having excellent mechanical properties and appearance properties can be obtained. In addition, if the glass fiber is not treated with a coupling agent, it can be added and used afterwards.

[0022] The average fiber diameter of the glass fiber (B) is preferably 3 to 15 μm, more preferably 3 to 10 μm, and further preferably 3 to 8 μm. The fiber diameter of the glass fiber is the diameter on the cross section perpendicular to the length direction of the glass fiber. In addition, when there is a maximum diameter and a minimum diameter on the cross section, the fiber diameter of the glass fiber refers to the maximum diameter. When the average fiber diameter is within the above range, the adhesion between the polyester resin and the glass fiber is improved, and the mechanical properties of the resin composition are improved.

[0023] The content of the glass fiber (B) in 100% by mass of the resin composition is 10 to 50% by mass, preferably 13 to 48% by mass, more preferably 15 to 45% by mass, and further preferably 18 to 42% by mass.

[0024] Potassium titanate (C) is potassium titanate represented by K2O·nTiO2 (where n is an integer selected from 1, 2, 4, 6, and 8). Among them, potassium titanate represented by K2O·6TiO2 with n=6 is preferred because it can be laser-marked with clear and high visibility. In particular, potassium titanate with a tunnel structure and less free potassium is preferred. Even if potassium titanate (C) contains crystal water, it will not be affected. In addition, it can be used after surface treatment with coupling agents such as silane, titanium, and aluminum.

[0025] Potassium titanate (C) may be either fibrous or particulate, or both may be used in combination, but is preferably fibrous. When potassium titanate (C) is fibrous, the average fiber diameter is preferably 0.05 to 1 μm, more preferably 0.05 to 0.9 μm, and further preferably 0.05 to 0.8 μm. When the average fiber diameter is lower than the above range, the operability is poor, and it is easy to contact with the glass fiber, so there is a concern about decreased mechanical properties; when it exceeds the above range, there is a concern about decreased laser imprintability. From the perspective of the ease of obtaining commercial products, the average fiber length is preferably 1 to 50 μm, more preferably 2 to 40 μm, and further preferably 3 to 30 μm.

[0026] When potassium titanate (C) is in the form of particles, the average particle size is preferably 0.5 to 15 μm, more preferably 1 to 13 μm, and further preferably 1.5 to 10 μm. When the average particle size is below the above range, the operability is deteriorated and it is easy to contact with glass fibers, so there is a concern that the mechanical properties are reduced; when the average particle size exceeds the above range, there is a concern that the laser engraving property is reduced.

[0027] In 100% by mass of the resin composition, the content of potassium titanate (C) needs to be 0.1 to 10% by mass, preferably 0.2 to 8% by mass, and more preferably 0.3 to 5% by mass. When the content is lower than the above range, the imprinting performance is poor. On the other hand, even if the content exceeds the above range, not only can the imprinting performance not be improved, but there is also a concern that the mechanical properties of the resin composition may be reduced.

[0028] When imparting flame retardancy to the resin composition for laser marking of the present invention, a non-halogen flame retardant (D) may be contained. As the non-halogen flame retardant (D), for example, a phosphorus flame retardant may be used. As the phosphorus flame retardant, there may be mentioned: red phosphorus compounds, diphosphine metal salts, reaction products composed of melamine and phosphoric acid, phosphazene compounds and phosphinic acid derivatives, which may be used alone or in combination.

[0029] In addition, in the laser marking resin composition of the present invention, non-phosphorus flame retardants can also be used as non-halogen flame retardants. In addition, phosphorus flame retardants and non-phosphorus flame retardants can also be used together. Examples of non-phosphorus flame retardants include nitrogen flame retardants, silicon flame retardants, metal hydroxides, metal boron oxides, and the like.

[0030] In 100% by mass of the resin composition, the content of the non-halogen flame retardant (D) is preferably 1 to 30% by mass, more preferably 3 to 27% by mass, and further preferably 5 to 24% by mass. When the content is lower than the above range, the desired high flame retardancy cannot be obtained. In addition, when it is more than the above range, the physical properties decrease, which is prone to cause problems. In addition, it is not preferred in terms of economy.

[0031] The resin composition for laser marking of the present invention preferably further contains a stabilizer. As the stabilizer, organic antioxidants such as hindered phenol antioxidants, sulfur antioxidants, phosphorus antioxidants, heat stabilizers, hindered amines, benzophenones, imidazoles, and other light stabilizers, ultraviolet absorbers, metal passivators, copper compounds, alkali metal halides, etc. can be cited. Among them, copper compounds are preferred. Stabilizers can be used alone or in combination. In addition, in 100% by mass of the resin composition, the content of the stabilizer is preferably 5% by mass or less, more preferably 4% by mass or less, and further preferably 3% by mass or less.

[0032] Examples of copper compounds that can be used as stabilizers include copper salts of organic carboxylic acids such as cuprous chloride, cuprous bromide, cuprous iodide, cupric chloride, cupric bromide, cupric iodide, copper phosphate, copper pyrophosphate, copper sulfide, copper nitrate, and copper acetate. The copper compound may be used alone or in combination of several.

[0033] For the purpose of modifying the properties such as impact resistance and flexibility, the resin composition for laser marking of the present invention may further contain an olefin compound. The olefin compound preferably has a carboxylic acid group and / or a carboxylic anhydride group. As such an olefin compound, for example, modified polyolefins, modified styrene copolymers, etc. can be cited. In 100% by mass of the resin composition, the content of the olefin compound is preferably 3% by mass or more, more preferably 6% by mass or more. In addition, the upper limit of the content of the olefin compound is preferably 20% by mass or less, more preferably 15% by mass or less, and further preferably 10% by mass or less.

[0034] In addition to the aforementioned glass fiber (B), the resin composition for laser marking of the present invention may also contain a known reinforcing material. Here, the reinforcing material refers to a substance that can improve the mechanical properties, specifically the mechanical properties of the molded product obtained by forming particles. The shape of the reinforcing material is not particularly limited, for example, it can be fibrous or particulate. As the type of reinforcing material, it is not particularly limited, for example, it can be cited: needle-shaped wollastonite, mica, talc, uncalcined clay, whiskers (except whiskers of potassium titanate), carbon fiber, ceramic fiber, silicon dioxide, aluminum oxide, kaolin, quartz, powdered glass (grinding fiber), graphite, glass flakes, calcium carbonate, barium sulfate, carbon black, metal powder, etc. The reinforcing material can be used alone or in combination. In 100% by mass of the resin composition, the content of reinforcing materials other than the glass fiber (B) is preferably less than 20% by mass.

[0035] The resin composition for laser marking of the present invention may further contain additives (E) such as a release agent, a crystal nucleating agent, a lubricant, a flame retardant, an antistatic agent, a pigment, a dye, etc. Among these additives (E), one or any combination can be selected for use. As a release agent, there can be mentioned: long-chain fatty acids or their esters, metal salts, amide compounds, polyethylene waxes, silicones, polyethylene oxides, etc. In 100% by mass of the resin composition, the content of these additives (E) is preferably 0.01% by mass or more, more preferably 0.05% by mass or more. In addition, in 100% by mass of the resin composition, the upper limit of the content of these additives (E) is preferably 5.0% by mass or less, more preferably 3.0% by mass or less, and further preferably 1.0% by mass or less.

[0036] For the laser marking resin composition of the present invention, the total amount of the above-mentioned components (A), (B), (C) and (D) preferably accounts for 90% by mass or more of the resin composition, and more preferably accounts for 95% by mass or more. It should be noted that the above-mentioned components (A), (B) and (C) are essential components, and the component (D) is an optional component.

[0037] The laser marking resin composition of the present invention can also maintain high mechanical properties when mixed with a non-halogen flame retardant (D). Specifically, the laser marking resin composition of the present invention can also achieve a high bending strength of more than 165MPa when further containing 1 to 30% by mass of a non-halogen flame retardant (D). Therefore, the laser marking resin composition of the present invention can be particularly preferably used for applications such as electrical / electronic components, mechanical structural components, and automotive components that require both high flame retardancy and high mechanical properties.

[0038] The method for producing the laser marking resin composition of the present invention is not particularly limited, and for example, a melt kneading extrusion method can be used, which can accurately control the mixing amount of each component of the present invention within the above-mentioned predetermined range. In this method, a single-screw extruder or a twin-screw extruder is preferably used.

[0039] When resin pellets having greatly different shapes, apparent specific gravity, friction coefficient, etc. are added to the mixed resin pellets from the hopper part of the extruder, it is preferred to mix the polyester resin (A) with other components in advance and add them to the hopper part of the extruder, and then add the glass fiber (B) and potassium titanate (C) by side feeding.

[0040] For molded products composed of the resin composition for laser marking of the present invention, or molded products such as resins, ceramics, and metals coated with the relevant resin composition by printing, coating, multiple molding, etc., it is easy to make clear markings by simply irradiating the desired position with laser light. In order to mark the desired shape, for example, there are: a method of adjusting the laser to a light spot of appropriate size and scanning the surface of the object; a method of forming a laser of the desired shape by masking the laser and then irradiating it to the surface of the object, etc. As the laser used, for example, there are: carbon dioxide lasers, ruby ​​lasers, semiconductor lasers, argon lasers, excimer lasers, YAG lasers, etc. Among them, Nd:YAG lasers are preferred, and scanning Nd:YAG lasers are particularly preferred. Example

[0041] The present invention will be described in further detail below based on examples, but the present invention is not limited to these examples. It should be noted that the various characteristics and physical property values ​​shown in the following examples and comparative examples were measured by the following test methods.

[0042] (1) Intrinsic viscosity (IV) of polyester resin: 0.1 g of the resin sample was dissolved in 25 ml of a mixed solvent of phenol / tetrachloroethane (mass ratio 6 / 4), and the viscosity was measured at 30°C using an Ubbelohde viscometer. (Unit: dl / g) (2) Bending strength: The bending strength of the test piece obtained by molding the resin composition pellets obtained in each of Examples and Comparative Examples was measured in accordance with ISO-178. (3) Laser marking ΔL: Regarding the laser marking property ΔL, a test piece obtained by molding the resin composition pellets obtained in each example and comparative example was laser marked under the following marking conditions, and the color difference ΔL between the marked portion and the base portion was measured according to the following measurement method. Marking conditions Equipment: Keyence Co., Ltd. 3-Axis UV laser marking MD-U1000C Marking conditions: laser power 20%; scanning speed 1000mm / s; Frequency 40kHz; Engraving times 1 time Determination of ΔL In accordance with JIS Z8722, a test was conducted using Tokyo Denshoku Precision Spectrophotometer TC-1500SX to measure the L of the marked portion that changed color upon laser irradiation and the L of the base portion, and ΔL was calculated from the following formula. ΔL = (L of the marking part) - (L of the base part) (4) Flammability test: The flammability of the test pieces obtained by molding the resin composition pellets obtained in each of the Examples and Comparative Examples was evaluated based on UL94. The thickness of the test piece was 1.6 mm.

[0043] The raw materials used in Examples and Comparative Examples are as follows. (A) Polyester resin (A-1): Polybutylene terephthalate resin (IV = 0.83 dl / g) (A-2): Polyethylene terephthalate resin (IV = 0.62 dl / g) (B): Glass fiber (B-1): "ECS03T-275H" manufactured by Nippon Electric Glass Co., Ltd. (fiber diameter 10.5μm, fiber length 3mm) (B-2): "CS 3DE-456" manufactured by Nitto Bosho Co., Ltd. (fiber diameter 6.5 μm, fiber length 3 mm) (C): Potassium titanate (C-1): "TISMO D" manufactured by Otsuka Chemical Co., Ltd. (fibrous, fiber diameter 0.5 μm, fiber length 15 μm) (C-2): "TIBREX RPN" manufactured by JFE Minerals Corporation (particle form, particle size 1.5 μm) (C-3): "TIBREX Type-IIM" manufactured by JFE Minerals Corporation (granular form, particle size 7 μm) (C'): "PF691" manufactured by Ishihara Sangyo Co., Ltd. (titanium oxide, particulate form, particle size 0.2 μm) (D) Non-halogen flame retardants (D-1) Aluminum phosphite / zinc tin trioxide / aluminum phosphite = 77 / 3 / 20 (E) Other additives (E-1) Magnesium stearate (mold release agent): "NP-1500" manufactured by Tamnan Chemical Industry Co., Ltd.

[0044] Examples 1 to 11, Comparative Examples 1 to 7 As shown in Table 1, each component except glass fiber and potassium titanate was pre-mixed using a tumble mixer, and the obtained pre-mixed mixture was supplied from the main feed port of a twin-screw extruder (TEM-1008, L / D=40). On the other hand, glass fiber and potassium titanate were supplied from the side feed port of the twin-screw extruder for melt mixing (main barrel temperature: 260°C, discharge rate: 300kg / hr). The obtained resin composition was discharged into a water bath to form strands, and the strands were micronized using a strand cutter to obtain resin composition particles. The obtained resin composition particles were dried and evaluated by the above method. The results are shown in Table 1.

[0045] [Table 1]

[0046] As clearly shown in Table 1, in Examples 1 to 11 containing specified amounts of polyester resin, glass fiber and potassium titanate, the bending strength is high and the contrast of laser engraving is also clear. On the other hand, in Comparative Examples 1 to 4 in which potassium titanate is replaced by titanium oxide, the bending strength (mechanical properties) decreases. This tendency is significant in Comparative Example 3 in which glass fiber is not mixed. In addition, in Comparative Example 5 in which potassium titanate is not mixed and in Comparative Example 6 in which the mixing amount of potassium titanate is too small, the laser engraving property (the presentation of engraving) is poor. Compared with Examples 1 to 8, in Comparative Example 7 in which the mixing amount of potassium titanate is too large, not only is no further improvement in laser engraving observed, but the bending strength (mechanical properties) is reduced.

[0047] In addition, although non-halogen flame retardants were mixed in Examples 6 to 8, high bending strength (mechanical properties) of the same level as those of Examples 1 to 5, 9 to 11 in which non-halogen flame retardants were not mixed were maintained. On the other hand, in Comparative Example 4, except for the use of titanium oxide instead of potassium titanate, the other mixing was the same as that of Example 6, but the bending strength (mechanical properties) was significantly reduced. Industrial Applicability

[0048] The polyester resin composition of the present invention can achieve high strength and high rigidity and can also produce characters or symbols with clear contrast when engraved with a laser, and therefore can be used in a wide range of applications such as electrical / electronic parts, mechanical structural parts, and automobile parts.

Claims

1. A resin composition for laser marking, characterized in that: The polyester resin (A) contains 20 to 80% by mass, the glass fiber (B) contains 10 to 50% by mass, and the potassium titanate (C) contains 0.1 to 10% by mass.

2. The resin composition for laser marking according to claim 1, characterized in that: Potassium titanate (C) is fibrous potassium titanate.

3. The resin composition for laser marking according to claim 1 or 2, characterized in that: The resin composition for laser marking further contains 1 to 30% by mass of a non-halogen flame retardant (D), and the flexural strength of the resin composition for laser marking is 165 MPa or more.

4. The resin composition for laser marking according to claim 1 or 2, characterized in that: The polyester resin (A) is polybutylene terephthalate or polyethylene terephthalate.

Citation Information

Patent Citations

  • Laser marking material developing black-based color upon irradiation with laser light and resin composition containing it

    JP1999001065A

  • Polyamide resin composition for laser marking and laser-marked polyamide resin molding

    JP2007098939A